Chemical composition of ferromanganese nodules near the Manihiki Plateau, Pacific Ocean - Peter Lonsdale (PANGAEA, 2023)
International Nickel Company (INCO) as a large operator of nickel mines investigated the mining potential of manganese nodules in the Pacific Ocean. It became interested in deep-ocean mining for manganese nodules as early as 1958, but it was not until late in 1971 that INCO opened its Ocean Mining Development office in Bellevue, WA. During those early years, INCO contracted with outside organizations such as the Scripps Institution Scripps Institution of Oceanography (SIO). This datatable reports on the particular assessment work made for INCO by Lonsdale P. from SIO in the vicinity of the Manihiki Plateau, Pacific Ocean. Manganese nodules were retrieved from the Manihiki Plateau area in the Pacific Ocean during cruise CH100 of the R/V Chain. Their chemical composition was determined using atomic absorption spectrophotometry.